Reproducción de la toboba de árbol, Bothriechis nigroviridis (Serpentes: Viperidae), en Costa Rica - Solórzano, Alejandro (1997)
The arboreal montane pitviper Bothriechis nigroviridis is distributed in the Central and Southeastem highlands of Costa Rica and Panamá. Eighty-six specimens were used mainly for morphometric analysis, reproductive cycle and distributional data Its activity pattem seems to be mainly nocturnal. Adult females are significantly longer than adult males. This species has a seasonal reproductive cycle, with timing of births closely related to the rainy season in Costa Rica (August-December). Neonates show identical color pattem to the adults. Courtship pattem is similar to that described for other pitvipers.